Transformasi Pendidikan Sebagai Pilar Kebangkitan Warga Komunitas: Telaah dari Al-Imran 3:113 - Yessi Handriyani; Hamim Ilyas (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The purpose of writing this work is the urgency of education as education for community members, community education and the meaning of honesty based on Surah Ali Imran 3:123, as well as the foundations of virtue in the community and the wisdom of honesty in the community in Islam. This research is a literature study that focuses on analyzing the concept of educational transformation in community members by referring to the verse Ali Imran 3:113. Data was obtained through library studies of the Al-Qur'an, educational literature, as well as analysis of relevant educational policy documents, then analyzed descriptively to understand the role of education in changing communities. Community-based education is a necessity in forming good character, facing moral challenges, and promoting lifelong learning, especially in the Islamic context which emphasizes unity and religious values. b) Surah Ali Imran 3:123 emphasizes the importance of education based on religious and moral values in forming the character and awareness of the Muslim community, making it a strong foundation for the development of a superior community. c) Surah Ali Imran 3:113 highlights honesty and moral values as key foundations in community education, creating strong character, a transparent environment, and support for justice. d) The wisdom of honesty in communities in Islam is that honesty leads individuals to heaven, builds trust, and forms a strong moral foundation in the community, so that it becomes a core value in Islamic community education.